GROWTH OF YBA2CU3O7-X FILMS ON SI WITH AL2O3 BUFFER LAYER AND ON LINBO3 BY INSITU METALORGANIC CHEMICAL VAPOR-DEPOSITION - YOM, SS; KANG, WN (PHYSICAL SOC REPUBLIC CHINA, 1992)
We present deposition of superconducting YBa2Cu3O7-x thin films on Si (100) substrate with an Al2O3 buffer, layer and LiNbO3 single crystal substrates by metalorganic chemical vapor deposition. Organomatallic sources of beta-diketonate complexes of Y(dpm)3, Ba(dpm)2, Cu(dpm)2, and aluminum isopropoxide were used as yttrium, barium, copper, and aluminum precursors, respectively. A resistive heated vertical cold-wall reaction chamber using N2O gas as an oxidizer was successful for depositing thin films of YBa2Cu3O7-x and an epitaxial Al2O3 buffer layer without post annealing. A buffer layer of MOCVD grown Al2O3 film on silicon (100) was found to be a gamma phase Al2O3 hetero-epitaxial film from the X-ray diffraction analysis. An As-deposited film on Al2O3/Si(100) substrate at a substrate temperature of 800 approximately 850-degrees-C showed superconducting behavior at T(c,zero) = 52 K. For YBa2Cu3O7-x/Al2O3/Si(100), the Al2O3 hetero-epitaxial buffer layer is a diffusion barrier between the superconducting film and the silicon substrate during high temperature growth. We also discuss in-situ MOCVD growth of an YBa2Cu3O7-x thin film on a z-cut LiNbO3 single crystalline substrate showing T(c,zero) = 85 K. In-situ formation of YBa2Cu3O7-x films on lattice mismatched LiNbO3 substrate is useful for future integrated optical device applications.
Keywords: O THIN-FILMS; SUPERCONDUCTING FILMS; EPITAXIAL-GROWTH; CU; SUBSTRATE; OXIDE